Wakaf Tunai Perspektif Syariah - Muhammad Tho’in; Iin Emy Prastiwi (Jurnal Ilmiah Ekonomi Islam, 2015)
The development of waqf implementation is now popular with the "cash waqf". Endowments in cash (cash waqf / waqf al nuqud) are waqf that a person, group of persons or institution or legal entity in the form of cash. This study aims to discuss how the cash waqf basis in sharia perspective.Waqf system is a concept that is not clearly and expressly mentioned in the Qur'an and hadith. Unlike the zakat that is clearly mentioned in the Qur'an. Scholarly opinion regarding waqf objects show that the terms of wakaf (must be objects, useful, not disposable, not haram substance and should belong to wakif perfectly). Cash waqf is not supported by the hadith in particular, and using verses from the Al Qur’an and Hadits is general. Therefore, the determination of the terms of waqf objects including ijtihadi region.Keywords: Cash waqf, Al Qur’an, Hadits